Better Not to Know? Emotion Regulation Fails to Benefit from Affective Cueing - Liu, Siwei; Vanderhasselt, Marie-Anne; Zhou, Juan; Schirmer, Annett (Frontiers in Human Neuroscience, 2016)
Often we know whether an upcoming event is going to be good or bad. But does that knowledge help us regulate ensuing emotions? To address this question, we exposed participants to alleged social feedback that was either positive or negative. On half the trials, a preceding cue indicated the feedback's affective quality. On the remaining trials, the cue was uninformative. In two different blocks, participants either appraised feedback spontaneously or down-regulated ensuing emotions using a controlled appraisal strategy. Event-related potentials (ERPs) recorded throughout both blocks revealed an increased late positive potential (LPP) during cue and feedback epochs when cues were affectively informative as compared to uninformative. Additionally, during feedback epochs only, informative, but not uninformative, cueing was associated with an appraisal effect whereby controlled appraisal reduced the LPP relative to spontaneous appraisal for negative feedback. There was an opposite trend for positive feedback. Together, these results suggest that informative cues allowed individuals to anticipate an emotional response and to adjust emotion regulation. Overall, however, informative cues seemed to have prolonged and intensified emotional responding when compared with uninformative cues. Thus, affective cueing appears to be contraindicated when individuals aim to reduce their emotions.